DEVELOPMENT OF MATHEMATICAL LITERACY-BASED TEACHING MATERIAL ON MATHEMATICS: PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS LITERASI MATEMATIKA - B., Firmansyah; Rais, Muhammad Rijali (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
This study aims to produce mathematics teaching material based on literacy. This teaching material is purposively developed and designated for all students, both students with low, medium, and high levels of literacy. Consequently, teachers could easily apply it classically in various learning environments in the class. The design uses the Plomp development model. The research subjects were class VII students of MTsN 3 Central Aceh with instruments in the form of expert validation sheets, practicality assessment sheets, and effectiveness assessments. This study describes the process of developing good-quality textbooks that have fulfilled the criteria of validity, practicality, and effectiveness. The results of expert validation on the material indicator, the average V index score was 0.81, the mathematical literacy indicator was 0.77, the illustration indicator was 0.74, the layout/format indicator was 0.8, and the language indicator was 0.8. Based on these results, it is known that the developed textbooks have fulfilled the valid category. The results of the recapitulation of the practicality questionnaire by the rater have a total score of 137 and a mean score of 45.66. Therefore, the teaching materials are categorized as Very Practical based on the categories used. The tests carried out in the test group showed that the mastery of learning after using textbooks was above 85%, which means that it fulfilled the excellent category, and indicates that the teaching materials developed are effective.